Cardiorespiratory Fitness, Metabolic Risk, and Inflammation in Children - Christodoulos, Antonios D. (Hindawi Publishing Corporation, 2012)
The aim of this study was to investigate the independent associations among cardiorespiratory fitness, metabolic syndrome (MetS), and C-reactive protein (CRP) in children. The sample consisted of 112 children (11.4  ±  0.4 years). Data was obtained for children's anthropometry, cardiorespiratory fitness, MetS components, and CRP levels. MetS was defined using criteria analogous to the Adult Treatment Panel III definition. A MetS risk score was also computed. Prevalence of the MetS was 5.4%, without gender differences. Subjects with low fitness showed significantly higher MetS risk (P < 0.001) and CRP (P < 0.007), compared to the high-fitness pupils. However, differences in MetS risk, and CRP between fitness groups decreased when adjusted for waist circumference. These data indicate that the mechanisms linking cardiorespiratory fitness, MetS risk and inflammation in children are extensively affected by obesity. Intervention strategies aiming at reducing obesity and improving cardiorespiratory fitness in childhood might contribute to the prevention of the MetS in adulthood.